ESTIMATION OF TURKISH ROAD TRANSPORT EMISSIONS AND EMISSION REDUCTION SCENARIOS - Ozoguz, Berk (YILDIZ TECHNICAL UNIV, 2008)
Turkish road transport emissions and fuel consumption originated from passenger cars were calculated for the year 2006 by using COPERT III simulation program. By taking these results as a baseline, some strategies were created to reduce fuel consumption and emissions. Strategies like; fleet renewal, faster urban traffic and prefering small engines have favourable effects on fuel consumption and exhaust emissions. While making arrengements about transport, energy and emission strategies these kinds of data should be considered for more effective results.
Keywords: Fuel consumption; emission estimation; road transport; copert III; Engineering